MPPT Charger with PWM Controller for Photovoltaic Based System - Vanitha, D.; P. Purushothaman; M. Rathinakimar (Asian Journal of Electrical Sciences, 2019)
Global energy demand is increasing exponentially. This increase in demand causes concern pertaining to the global energy crisis and allied environmental threats. The solution of these issues is seen in renewable energy sources. Solar energy is considered one of the major sources of renewable energy, available in abundance and also free of cost. Solar photo voltaic (PV) cells are used to convert solar energy in to unregulated electrical energy. These solar PV cells exhibition linear characteristics and give very low efficiency. Therefore, it becomes essential to extract maximum power from solar PV cells using maximum power point tracking (MPPT). Perturb and observe (P&O) is one of such MPPT schemes. This paper aims to address the issue of the conventional P&O MPPT scheme under increase solar irradiation condition and its behavior under changed load condition using Digital PWM Controller.